HUBUNGAN DUKUNGAN KADER DENGAN MINAT PEMANFAATAN POSYANDU REMAJA DI PUSKESMAS WILAYAH KECAMATAN GU KABUPATEN BUTON TENGAH - Samsia Winda; Adius Kusnan; Asriati Asriati (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
The implementation of school-age and adolescent health services is carried out through a youth-friendly service approach or known as the Youth Care Health Service (PKPR). The Youth Integrated Healthcare Center activities at the Gu District Health Center consist of 14 posts consisting of UPTD Public health center Gu, UPTD Public health center Rahia and UPTD Public health center Wadiabero. The purpose of the youth Integrated Healthcare Center is to improve the health status of adolescents and healthy behavior of adolescents. The aims study to analyze the relationship between adolescents' interest in using youth Integrated Healthcare Center at the Public Health Center in Gu District, Central Buton Regency. Analytical research with a Cross Sectional Study approach. The research location is the Youth Integrated Healthcare Center at the GU District Health Center. The research population was teenagers in the Gu District Health Center in 2021 spread across 14 Integrated Healthcare Center as many as 2,863 teenagers. The research sample was 351 people. Research results: Based on the results of the Chi-square test statistical analysis shows that significant relationship with interest in the use of youth Integrated Healthcare Center, the support of adolescent cadres obtained p-value = 0.000. Interest in the use of youth Integrated Healthcare Center has a significant relationship with youth cadres.